Preliminary Study: Analysis of the Need for Physics E-Modules as Guided Inquiry-Based Teaching Materials at MAN 1 Mandailing Natal - Rahmi Habibah; Ahmad Fauzi (Jurnal Penelitian Pendidikan IPA, 2023)
This research was carried out to develop a learning resource type of learning media in the form of guided inquiry-based teaching materials. So, preliminary study research is needed which consists of literature study and field study. The type of research carried out was qualitative descriptive research. The data collection instruments for this research are interview sheets, teacher needs analysis questionnaires, and student needs analysis questionnaires. The teaching materials developed are in the form of (e-modules) electronic modules that can contain text, images and learning videos, as an independent learning effort that is arranged systematically. To create an e-module using the Canva application. A needs analysis is carried out to determine the learning resources used by teachers, obstacles when learning takes place, and the learning resources needed by students. The results of the analysis of teacher needs show that religious analysis is 83% in the good category, attitude analysis is 94% in the very good category, knowledge analysis is 65% in the sufficient category, performance analysis is 83% in the good category, analysis of learning difficulties is 58% in the poor category, material analysis teaching 50% in the poor category and model analysis 67% in the sufficient category. Furthermore, the results of the analysis of students' needs show that motivation analysis is 70% in the sufficient category, interest analysis is 50% in the poor category, attitude analysis is 81% in the good category, creative thinking analysis is 49% in the poor category and material analysis is 48% in the poor category. These results indicate the need to develop teaching materials in the form of e-modules based on guided inquiry on global warming.